TRANSPARENCY AND OPENNESS IN THE SYSTEM OF PRINCIPLES OF THE EUROPEAN ADMINISTRATIVE SPACE - Grybko O. V., (Pressing Problems of Public Administration, 2021)
Adaptation of the Ukrainian administrative system to European standards is one of the most important tasks of public administration reform. This should be the basis for Ukraine’s future membership in the EU, as the maximum compliance of national legislation with European standards is a basic condition for EU membership candidate.The European Union attaches great importance to the implementation of a number of principles in the context of the concept of a Common European Administrative Space (EAS), which can be divided into four categories:1) the rule of law (often defined as reliability and predictability, legitimacy or certainty within the law);2) openness and transparency;3) responsibility / accountability;4) efficiency and productivity.The EAS, which is based on these principles, provides for the introduction and application of a set of public administration standards, which are defined by law and used in practice through appropriate procedures and accountability mechanisms. In many EU member states, these principles are usually enshrined in the constitution and detailed in a number of laws.Thus, transparency and openness are central to the system of the European Administrative Space principles, as they are closely linked to all others - responsibility, efficiency, compliance with the law; without transparent public administration it is impossible for the community to perceive their decisions as fair. Openness and transparency are also essential tools for ensuring the rule of law, equality before the law and accountability. Public administration in Ukraine should primarily focus on the maximum implementation of these principles of the European administrative space in the practical activities of public authorities, in real administrative procedures.